Bubbles and Machines Gender, Information and Financial Crises - Lee, Mickey (Critical Digital and Social Media Studies, 2019)
Are financial crises embedded in IT? Can gender studies offer insights into financial reporting? Feminist theories and Science and Technology Studies (STS) can enrich a critique of financial crises in capitalism as the author argues their critical, political economic approaches to communication can help in understanding because they historicize technology and economy and how these are materially embedded. Current literature has neglected finance and capital's gendered aspect - even - the ideology of a 'crisis'. This book develops four themes: women as resources in financial markets and as producers of values; gender ideology and unequal distribution; machine production and distribution of financial information and the varied actuality of markets. Working with case histories of tulipmania, microcredit, Wall Street reporting and the role of 'screens', Bubbles and Machines argues that rather than calling financial crises human-made or inevitable they should be recognized as technological.